Restaurateurs’ context, decisions, and views on supporting sustainable seafood: Insights from Chile - Donlan, C. Josh; Sorice, Michael G.; Contreras-Drey, Francisco J.; Oyanedel, Rodrigo; Ávila-Thieme, M. Isidora; Gelcich, Stefan (Frontiers in Marine Science, 2022)
While restauranteurs are important actors in seafood systems, information on their decisions and views on sustainability is lacking. Using mixed methods, we explored Chilean restauranters’ contexts, decisions, and views on seafood sustainability. Menus in Chile are diverse and dominated by domestic and wild-caught sources. Restauranters are willing to participate in traceability programs, especially when it is for both sustainability and health safety reasons. Restauranters believe that seafood is an elite resource and high prices are inhibiting access. They also believe patrons care little about seafood sustainability yet are willing to pay a premium for it. This contradiction suggests a mechanism for activating values via situational factors. While demand and benefits for seafood traceability programs appear present, challenges threaten successful implementation. Complex socio-economic factors, such as affordability, elitism, and inequity, need to be integrated into traceability program design to contribute to the necessary transformation of seafood systems.